HUBUNGAN STATUS GIZI DENGAN KADAR PROLAKTIN SERUM IBU MENYUSUI - Diyan Indrayani (Jurnal Asuhan Ibu dan Anak, 2018)
Failure of exclusive breastfeeding contributes to the severity and death of infants and toddlers. The cause of the failure of exclusive breastfeeding is the lack of milk production. Prolactin is a hormone that plays an important role in milk production. One of the factors affecting breast feeding prolactin levels is nutritional status. Nutritional status determines a quality breastfeeding process. This study aims to analyze the relationship of maternal nutritional status with breastfeeding serum prolactin level. This research use cross sectional design. The sample of this research is postpartum primiparous mother who gave birth at Puskesmas Kota Bandung with 48 people who fulfill inclusion criteria and chosen by consecutive sampling. The study was conducted from March to May 2016. Data analysis using Kruskal wallis followed by Post Hoc analysis with Mann Whitney. The results showed that there was a significant difference in maternal serum prolactin level between low and high nutrition status group and moderate vs high (p <0.05), but there was no significant difference in serum prolactin level in the low to moderate nutritional status group (p> 0.05). In breastfeeding mothers prolactin levels are influenced by several factors both physiological, psychological and physical. In this research, it can be concluded that there is difference of maternal serum prolactin level between mother with low and high nutrition status and medium and high nutrition status group.